A Task-Oriented Study On The Influencing Effects of Query-Biased Summarisation In Web Searching - White, Ryen W.; Jose, Joemon M.; Ruthven, Ian (Information Processing and Management (IP&M), 2002)
The aim of the work described in this paper is to evaluate the influencing effects of query-biased summaries in web searching. For this purpose, a summarization system has been developed, and a summary tailored to the user's query is generated automatically for each document retrieved. The system aims to provide both a better means of assessing document relevance than titles or abstracts typical of many web search result lists. Through visiting each result page at retrieval-time, the system provides the user with an idea of the current page content and thus deals with the dynamic nature of the web. To examine the effectiveness of this approach, a task-oriented, comparative evaluation between four different web retrieval systems was performed; two that use query-biased summarization, and two that use the standard ranked titles/abstracts approach. The results from the evaluation indicate that query-biased summarization techniques appear to be more useful and effective in helping users gauge document relevance than the traditional ranked titles/abstracts approach. The same methodology was used to compare the effectiveness of two of the web's major search engines; AltaVista and Google.